Ostracism in alliances of teams and individuals: Voting, exclusion, contribution, and earnings - Stephan Huber; Jochen Model; Silvio Städter (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2019)
Alliances often provide a collective good among their allies. This article offers laboratory experimental evidence that the possibility to vote for the exclusion of non-cooperating allies, i.e. ostracism, can be a powerful negative referendum to increase allies' contributions to the collective good. However, it is found that ostracism does not necessarily increase earnings in a public goods game. In particular, it is shown that the ostracism mechanism is used differently by individuals. While ostracism increases contributions irrespective of the game is played with a alliances of individuals or teams as the decision makers, the earnings do not statistically significant increase in alliances of individuals. This result can be explained with different voting patterns. Compared to individuals, teams vote and in turn exclude significantly less in early periods but more in later periods of the game. Thus, negative earnings effects of ostracism, i.e., excluded players can neither contribute to the collective good nor receive from the collective good, are found to be less severe in alliances of teams.
Keywords: C91; C92; H41; 330; alliances; team decision; public good; collective good; ostracism; exclusion; experiment